Green Finance in Indonesia: A Literature Review - Risna Wati; Muhammad Iqbal Fasa (Scimadly Publishing, 2024)
The banking world is also adopting the concept of green finance, which basically encourages that any economic effort minimize its negative impact on the environment. In the banking industry, this greening movement is referred to as green banking. This green movement is not only limited to financing, but also Islamic banking programs that provide financing for businesses or activities that can damage or pollute the environment. This study is a type of qualitative research that uses a library research approach, which involves collecting information through observation. Researchers use literature research as supporting literature to obtain data and information about books or other sources related to Green Finance. Key findings from the analysis include the importance of green finance guidelines and frameworks in encouraging sustainable financial practices, the role of central banks in supporting the transition to a low-carbon economy through initiatives such as green banking and green bond issuance, and the importance of soft power measures to steer investment preferences toward green finance.